Halogen-free flame-retardant adhesive and preparation method thereof
By using halogen-free flame retardant and specific modified polymers in emulsion adhesives, a stable three-dimensional network structure is formed, which solves the problems of flammability and environmental pollution of emulsion adhesives, and achieves high-performance halogen-free flame retardant Adhesive.
Patent Information
- Application Number
- CN202411442748.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-18
AI Technical Summary
Emulsion adhesives are flammable, and the flame spreads rapidly, producing thick smoke and toxic gases, and the addition of halogen-containing flame retardants will cause environmental pollution.
Halogen-free flame retardants and specific modified polymers, such as vinyl hydrophilic group modified terminal amino hyperbranched polysulfone amine, quaternary ammonium salt-15 modified Ag-MOFs metal organic frame, vinyl modified water-soluble The quantum dots of boron nitride form a stable three-dimensional network structure through copolymerization and cross-linking reaction, enhancing the flame retardant performance of the adhesive.
It realizes the easy stickiness, tearability and good flame retardant properties of halogen-free flame retardant adhesives. After removal, there is no residual glue, high mechanical strength, good weather resistance, good antibacterial properties, and excellent flame retardant properties.
Smart Images

Figure BDA0005086794330000041 
Figure BDA0005086794330000051 
Figure BDA0005086794330000052
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and particularly relates to a halogen-free flame-retardant adhesive and a preparation method thereof. Background Art
[0002] Emulsion adhesives are one of the development trends of adhesives. Compared with solvent-based adhesives, they have the characteristics of no solvent release, environmental compliance, low cost and safe use. EVA copolymer emulsion adhesives are often used in leather processing, construction, coatings, textiles, laminating adhesives and paper processing and other industries. However, like most polymers, emulsion adhesives have the disadvantages of being flammable, fast flame propagation speed, producing thick smoke and toxic gases. Therefore, improving the flame retardant properties of emulsion adhesives has become an urgent problem to be solved. The addition of halogen-containing flame retardants will cause the polymer to generate a large amount of smoke and toxic gases when burning, causing secondary pollution to the environment. Polyacrylate emulsion is a class of high molecular polymer materials with good water solubility. It is mainly prepared by emulsion polymerization using acrylic acid compounds or methacrylate compounds as reaction raw materials. Polyacrylate emulsions have good mechanical stability, weather resistance, film-forming properties, chemical stability, corrosion resistance, etc., and are widely used in coatings, adhesives, multifunctional membranes, medical polymer materials, nanomaterials and other fields. With the development of emulsion polymerization technology, polyacrylate emulsion coatings can be used as the basic material of water-based coatings and are widely used in water-based anti-corrosion coatings, architectural coatings, wood coatings and other industries. At the same time, polyacrylate emulsions are often used as adhesives because of their good adhesion and excellent bonding properties.
[0003] A Chinese patent with application number CN201910609571.8 discloses a conductive halogen-free flame-retardant acrylic pressure-sensitive adhesive, which is composed of the following raw materials in parts by mass: 90-110 parts of a multi-acrylate copolymer monomer, 10-30 parts of an allyl phosphate monomer, 5-10 parts of a cross-linked modified monomer, 150-300 parts of deionized water, 2-6 parts of an initiator, 2-7 parts of an emulsifier, 20-30 parts of a phosphorus-containing filler, and 20-40 parts of an inorganic filler. The adhesive prepared by the present invention is a liquid single-component package with a long storage period and will not deteriorate for 12 months; the adhesive obtained by the invention is a water-based adhesive with no solvent volatilization and pollution, but its flame retardant effect is poor. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a halogen-free flame retardant adhesive and a preparation method thereof.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A halogen-free flame retardant adhesive is composed of the following raw materials in parts by weight: 10-20 parts of hydroxyethyl acrylate, 5-10 parts of acrylic acid, 500-800 parts of butyl acrylate, 10-15 parts of vinyl hydrophilic group modified terminal amino hyperbranched polysulfone amine, 2-5 parts of quaternary ammonium salt-15 modified Ag-MOFs metal organic framework, 2-5 parts of vinyl modified water-soluble boron nitride quantum dots, 5-8 parts of initiator, 10-20 parts of halogen-free flame retardant, 1-3 parts of crosslinking agent, 2-3 parts of defoaming agent, 5-10 parts of thickener and 350-450 parts of deionized water.
[0007] Furthermore, the initiator is at least one of ammonium bicarbonate, ammonium persulfate, and tert-butyl hydroperoxide.
[0008] Furthermore, the halogen-free flame retardant is at least one of triphenyl phosphate, triisopropylphenyl phosphate, melamine polyphosphate, and a condensate of phosphate ester.
[0009] Furthermore, the cross-linking agent is at least one of aziridine and silane coupling agent KH-560.
[0010] Furthermore, the defoaming agent is at least one of polydimethylsiloxane and polymethylsiloxane.
[0011] Furthermore, the thickener is polybutyl acrylate.
[0012] A method for preparing a halogen-free flame retardant adhesive comprises the following steps:
[0013] S1: Mix hydroxyethyl acrylate, acrylic acid and butyl acrylate according to the set weight proportions, add 150-200 parts of deionized water and stir for 10-20 minutes to obtain a pre-emulsion;
[0014] S2: In a 60°C environment, under the protection of nitrogen, add 50% of the initiator to 200-250 parts of deionized water while stirring, raise the temperature to 70°C, add 50% of the pre-emulsion, 50% of the vinyl hydrophilic group-modified terminal amino hyperbranched polysulfone amine, 50% of the quaternary ammonium salt-15-modified Ag-MOFs metal organic framework and 50% of the vinyl modified water-soluble boron nitride quantum dots, and stir for 30-45 minutes;
[0015] S3: Raise the temperature to 85°C, add the remaining 50% initiator, 50% vinyl hydrophilic group modified terminal amino hyperbranched polysulfone amine, 50% quaternary ammonium salt-15 modified Ag-MOFs metal organic framework and 50% vinyl modified water-soluble boron nitride quantum dots, and add the remaining 90% pre-emulsion dropwise within 2-3 hours while stirring, and keep warm for 2-2.5 hours;
[0016] S4: Cooling to 50° C., adding a halogen-free flame retardant, a cross-linking agent, a defoaming agent, and a thickener, stirring for 20-30 minutes, and naturally cooling to room temperature to obtain the halogen-free flame retardant adhesive.
[0017] Furthermore, in step S1, the rotation speed of the stirring process is 800-1000 r / min; in steps S2 to 3, the rotation speed of the stirring process is 600-800 r / min; in step S4, the rotation speed of the stirring process is 300-500 r / min.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The halogen-free flame retardant adhesive provided by the present invention is an emulsion adhesive, which is halogen-free, environmentally friendly and safe. By reasonably controlling the raw material ratio, the adhesive of the present invention has easy adhesion, easy tearing and good flame retardancy during use, and no residual adhesive is left after removal; the vinyl hydrophilic group-modified terminal amino hyperbranched polysulfone amine, quaternary ammonium salt-15 modified Ag-MOFs metal organic framework, and vinyl modified water-soluble boron nitride quantum dots added by the present invention can undergo copolymerization and cross-linking reactions under the action of an initiator to form a stable three-dimensional network structure, thereby enhancing the strength of the adhesive, and the halogen-free flame retardant of the present invention can be connected to the formed three-dimensional network in the form of a chemical bond, thereby enabling the flame retardant to better exert its flame retardancy and enhancing the flame retardant performance of the adhesive.
[0020] 2. In the present invention, the added vinyl hydrophilic group-modified terminal amino hyperbranched polysulfoneamine contains sulfone groups, which can improve the weather resistance and impact resistance of the adhesive of the present invention, and the polynitrogen structure therein can further improve the flame retardancy of the adhesive.
[0021] 3. In the present invention, the added quaternary ammonium salt-15 modified Ag-MOFs metal organic framework also has good antibacterial properties, wherein the quaternary ammonium salt-15 can improve the chemical resistance, water resistance and weather resistance of the adhesive under the action of electronic effect and steric effect.
[0022] 4. The present invention provides a method for preparing a halogen-free flame-retardant adhesive, which improves the comprehensive performance of the adhesive by strictly controlling the reaction temperature, time, stirring rate, etc. DETAILED DESCRIPTION
[0023] The present invention is further described below in conjunction with preferred embodiments. The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values; for numerical ranges, the endpoint values of each range, the endpoint values of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein; the materials, reagents, etc. used in the following embodiments, unless otherwise specified, can be obtained from commercial channels; the experimental methods in the following embodiments, unless otherwise specified, are all conventional methods.
[0024] Example 1
[0025] This embodiment provides a halogen-free flame retardant adhesive, which is composed of the following raw materials in parts by weight:
[0026] Table 1 Halogen-free flame retardant adhesive components
[0027]
[0028]
[0029] This embodiment also provides a method for preparing a halogen-free flame retardant adhesive, comprising the following steps:
[0030] S1: Mix hydroxyethyl acrylate, acrylic acid and butyl acrylate according to the set weight proportions, add 180 parts of deionized water, and stir at a speed of 900 r / min for 15 minutes to obtain a pre-emulsion;
[0031] S2: In a 60°C environment, under the protection of nitrogen, add 50% of ammonium bicarbonate to 220 parts of deionized water while stirring at a speed of 700 r / min, raise the temperature to 70°C, add 50% of the pre-emulsion, 50% of the vinyl hydrophilic group-modified terminal amino hyperbranched polysulfone amine, 50% of the quaternary ammonium salt-15-modified Ag-MOFs metal organic framework and 50% of the vinyl modified water-soluble boron nitride quantum dots, and stir at a speed of 700 r / min for 40 minutes;
[0032] S3: Raise the temperature to 85°C, add the remaining 50% of ammonium bicarbonate, 50% of vinyl hydrophilic group-modified terminal amino hyperbranched polysulfone amine, 50% of quaternary ammonium salt-15-modified Ag-MOFs metal organic framework and 50% of vinyl modified water-soluble boron nitride quantum dots, add the remaining 90% of the pre-emulsion dropwise within 2.5 hours while stirring at a speed of 700 r / min, and keep warm for 2.2 hours;
[0033] S4: cooling to 50° C., adding triisopropylphenyl phosphate, aziridine, polydimethylsiloxane and polybutyl acrylate, stirring at a speed of 400 r / min for 25 min, and naturally cooling to room temperature to obtain the halogen-free flame retardant adhesive.
[0034] Example 2
[0035] This embodiment provides a halogen-free flame retardant adhesive, which is composed of the following raw materials in parts by weight:
[0036] Table 2 Halogen-free flame retardant adhesive components
[0037]
[0038]
[0039] This embodiment also provides a method for preparing a halogen-free flame retardant adhesive, comprising the following steps:
[0040] S1: Mix hydroxyethyl acrylate, acrylic acid and butyl acrylate according to the set weight proportions, add 200 parts of deionized water, and stir at a speed of 1000 r / min for 20 minutes to obtain a pre-emulsion;
[0041] S2: In a 60°C environment, under the protection of nitrogen, add 50% of ammonium persulfate to 250 parts of deionized water while stirring at a speed of 800 r / min, raise the temperature to 70°C, add 50% of the pre-emulsion, 50% of the vinyl hydrophilic group-modified terminal amino hyperbranched polysulfone amine, 50% of the quaternary ammonium salt-15-modified Ag-MOFs metal organic framework and 50% of the vinyl modified water-soluble boron nitride quantum dots, and stir at a speed of 800 r / min for 45 minutes;
[0042] S3: Raise the temperature to 85°C, add the remaining 50% of ammonium persulfate, 50% of vinyl hydrophilic group-modified terminal amino hyperbranched polysulfone amine, 50% of quaternary ammonium salt-15-modified Ag-MOFs metal organic framework and 50% of vinyl modified water-soluble boron nitride quantum dots, add the remaining 90% of the pre-emulsion dropwise within 3 hours while stirring at a speed of 800 r / min, and keep warm for 2.5 hours;
[0043] S4: cooling to 50° C., adding triisopropylphenyl phosphate, silane coupling agent KH-560, polydimethylsiloxane, polymethylsiloxane, and polybutyl acrylate, stirring at a speed of 500 r / min for 30 min, and naturally cooling to room temperature to obtain the halogen-free flame retardant adhesive.
[0044] Example 3
[0045] This embodiment provides a halogen-free flame retardant adhesive, which is composed of the following raw materials in parts by weight:
[0046] Table 3 Halogen-free flame retardant adhesive components
[0047] Hydroxyethyl acrylate 10 servings acrylic acid 5 servings Butyl acrylate 500 copies Vinyl hydrophilic group modified amino-terminated hyperbranched polysulfone amine 10 servings Quaternary ammonium salt-15 modified Ag-MOFs metal organic framework 2 servings Vinyl-modified water-soluble boron nitride quantum dots 2 servings Tert-Butyl Hydroperoxide 5 servings Triphenyl phosphate 10 servings Aziridine 0.5 serving Silane coupling agent KH-560 0.5 serving Polymethylsiloxane 2 servings Polybutyl acrylate 5 servings Deionized water 350 copies
[0048] This embodiment also provides a method for preparing a halogen-free flame retardant adhesive, comprising the following steps:
[0049] S1: Mix hydroxyethyl acrylate, acrylic acid and butyl acrylate according to the set weight proportions, add 150 parts of deionized water, and stir at a speed of 800 r / min for 10 min to obtain a pre-emulsion;
[0050] S2: In a 60°C environment, under the protection of nitrogen, add 50% of tert-butyl hydroperoxide to 200 parts of deionized water while stirring at a speed of 600 r / min, raise the temperature to 70°C, add 50% of the pre-emulsion, 50% of the vinyl hydrophilic group-modified terminal amino hyperbranched polysulfone amine, 50% of the quaternary ammonium salt-15-modified Ag-MOFs metal organic framework and 50% of the vinyl modified water-soluble boron nitride quantum dots, and stir at a speed of 600 r / min for 30 minutes;
[0051] S3: Raise the temperature to 85°C, add the remaining 50% of tert-butyl hydroperoxide, 50% of vinyl hydrophilic group-modified terminal amino hyperbranched polysulfone amine, 50% of quaternary ammonium salt-15-modified Ag-MOFs metal organic framework and 50% of vinyl modified water-soluble boron nitride quantum dots, add the remaining 90% of the pre-emulsion dropwise within 2 hours while stirring at a speed of 600 r / min, and keep warm for 2 hours;
[0052] S4: cooling to 50° C., adding triphenyl phosphate, aziridine, silane coupling agent KH-560, polymethylsiloxane, and polybutyl acrylate, stirring at a speed of 300 r / min for 20 min, and naturally cooling to room temperature to obtain the halogen-free flame retardant adhesive.
[0053] In this embodiment, the initiator can also be selected from a mixture of ammonium bicarbonate, ammonium persulfate, and tert-butyl hydroperoxide; the halogen-free flame retardant can also be selected from one or a mixture of triphenyl phosphate, triisopropylphenyl phosphate, melamine polyphosphate, and condensates of phosphate esters.
[0054] Comparative Example 1
[0055] The difference from Example 1 is that:
[0056] This comparative example does not contain vinyl hydrophilic group-modified amino-terminated hyperbranched polysulfoneamine, quaternary ammonium salt-15-modified Ag-MOFs metal organic framework, or vinyl-modified water-soluble boron nitride quantum dots.
[0057] Comparative Example 2
[0058] The difference from Example 1 is that:
[0059] This comparative example does not contain the amino-terminated hyperbranched polysulfoneamine modified with a vinyl hydrophilic group.
[0060] Comparative Example 3
[0061] The difference from Example 1 is that:
[0062] This comparative example does not contain quaternary ammonium salt-15 modified Ag-MOFs metal organic framework.
[0063] Comparative Example 4
[0064] The difference from Example 1 is that:
[0065] In the preparation method of this comparative example, the stirring rate is 500 r / min.
[0066] Implementation effect evaluation:
[0067] The excellent effects achieved by the present invention are further illustrated by specific experiments below:
[0068] The halogen-free flame retardant adhesives prepared in Examples 1-3 and Comparative Examples 1-4 were poured into a mold and dried naturally at room temperature for 24 hours. After the surface was dried, they were placed in an oven at 100° C. for 12 hours. After natural cooling, halogen-free flame retardant adhesive samples were obtained, and the following performance tests were performed on the samples:
[0069] Initial adhesion test:
[0070] The halogen-free flame retardant adhesive was diluted with deionized water to a solid content of about 30%, and the viscosity of each halogen-free flame retardant adhesive was measured at 25°C using a rotational viscometer.
[0071] Film 180° peel strength test:
[0072] Use a 50μm applicator to evenly coat the halogen-free flame retardant adhesive on a PI film with a width of 25mm and a length of 150mm to make a strip sample. Place the prepared sample in a 100℃ oven to dry for 7-10min, take out the halogen-free flame retardant adhesive tape and place it on a smooth glass surface. After cooling to room temperature, stick it on the tinplate, press it back and forth 3 times with a roller, and then gently press it evenly with the fingertips. Use an electronic tensile tester with a test speed of 300mm / min and perform 180° peeling.
[0073] Thermal stability analysis:
[0074] In a nitrogen atmosphere, a thermogravimetric analyzer was used for testing. 5-10 mg of dry adhesive was placed in a crucible. The test range was 50-600°C and the heating rate was 10°C / min.
[0075] Mechanical properties test:
[0076] The film samples to be tested were cut into 75mm×4mm 5A dumbbell specimens and placed at room temperature for 7 days to eliminate internal stress. The tensile properties of the samples were tested using an electronic universal testing machine with a tensile rate of 100mm / min. Each sample was tested 5 times in parallel and the average value was taken.
[0077] Residue test:
[0078] Make the adhesive into tape and test its adhesive residue.
[0079] Oxygen index test:
[0080] The oxygen index of the halogen-free flame retardant adhesive sample is tested according to GB / T 2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test".
[0081] Antimicrobial test:
[0082] Staphylococcus aureus and Escherichia coli were used as test strains. A bacterial solution diluted to 106 / mL after culturing the strains was taken, and then the bacterial solution was smeared on an agar plate and cultured in an incubator at 37°C for 12 hours. The adhesives prepared in Examples 1-3 and Comparative Examples 1-4 were made into samples with a diameter of 5 mm and a thickness of 1 mm. The samples were immersed in a 10% ethanol solution for 24 hours. After drying, the samples were placed on agar plates respectively, and cultured in an incubator again for 12 hours. After taking out, the diameter of the antibacterial ring was measured.
[0083] The test results are shown in the table below:
[0084] Table 4 Test results statistics
[0085]
[0086]
[0087] It can be seen from the above data that the halogen-free flame retardant adhesive provided by the present invention is easy to stick and tear and has good flame retardancy, and there is no residual adhesive after removal. The adhesive of the present invention has high mechanical strength, good weather resistance, good antibacterial performance, and excellent flame retardancy.
[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept of the present invention, which all fall within the protection scope of the present invention.
Claims
1. A halogen-free flame retardant adhesive, characterized in that: The invention is composed of the following raw materials in parts by weight: 10-20 parts of hydroxyethyl acrylate, 5-10 parts of acrylic acid, 500-800 parts of butyl acrylate, 10-15 parts of vinyl hydrophilic group modified terminal amino hyperbranched polysulfone amine, 2-5 parts of quaternary ammonium salt-15 modified Ag-MOFs metal organic framework, 2-5 parts of vinyl modified water-soluble boron nitride quantum dots, 5-8 parts of initiator, 10-20 parts of halogen-free flame retardant, 1-3 parts of crosslinking agent, 2-3 parts of defoaming agent, 5-10 parts of thickener and 350-450 parts of deionized water.
2. The halogen-free flame retardant adhesive according to claim 1, characterized in that: The initiator is at least one of ammonium bicarbonate, ammonium persulfate and tert-butyl hydroperoxide.
3. The halogen-free flame retardant adhesive according to claim 1, characterized in that: The halogen-free flame retardant is at least one of triphenyl phosphate, triisopropylphenyl phosphate, melamine polyphosphate, and a condensate of phosphate ester.
4. The halogen-free flame retardant adhesive according to claim 1, characterized in that: The cross-linking agent is at least one of aziridine and silane coupling agent KH-560.
5. The halogen-free flame retardant adhesive according to claim 1, characterized in that: The defoaming agent is at least one of polydimethylsiloxane and polymethylsiloxane.
6. The halogen-free flame retardant adhesive according to claim 1, characterized in that: The thickener is polybutyl acrylate.
7. A method for preparing a halogen-free flame retardant adhesive according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: Mix hydroxyethyl acrylate, acrylic acid and butyl acrylate according to the set weight proportions, add 150-200 parts of deionized water and stir for 10-20 minutes to obtain a pre-emulsion; S2: In a 60°C environment, under the protection of nitrogen, add 50% of the initiator to 200-250 parts of deionized water while stirring, raise the temperature to 70°C, add 50% of the pre-emulsion, 50% of the vinyl hydrophilic group-modified terminal amino hyperbranched polysulfone amine, 50% of the quaternary ammonium salt-15-modified Ag-MOFs metal organic framework and 50% of the vinyl modified water-soluble boron nitride quantum dots, and stir for 30-45 minutes; S3: Raise the temperature to 85°C, add the remaining 50% initiator, 50% vinyl hydrophilic group modified terminal amino hyperbranched polysulfone amine, 50% quaternary ammonium salt-15 modified Ag-MOFs metal organic framework and 50% vinyl modified water-soluble boron nitride quantum dots, and add the remaining 90% pre-emulsion dropwise within 2-3 hours while stirring, and keep warm for 2-2.5 hours; S4: Cooling to 50° C., adding a halogen-free flame retardant, a cross-linking agent, a defoaming agent, and a thickener, stirring for 20-30 minutes, and naturally cooling to room temperature to obtain the halogen-free flame retardant adhesive.
8. The method for preparing a halogen-free flame retardant adhesive according to claim 7, characterized in that: In step S1, the rotation speed of the stirring process is 800-1000r / min; in steps S2 to 3, the rotation speed of the stirring process is 600-800r / min; in step S4, the rotation speed of the stirring process is 300-500r / min.
Citation Information
Patent Citations
Conductive halogen-free flame retardant acrylic pressure-sensitive adhesive
CN110343482A